SARS-CoV-2 INFECTED PATIENTS: FROM A HEMATOLOGIST PERSPECTIVE: COVID-19 and Hematology - Kreidieh, Firas; Temraz, Sally (Mediterranean Journal of Hematology and Infectious Diseases, 2020)
Introduction: According to the World Health Organization (WHO), COVID-19 has become a Public Health Emergency of International Concern (PHEIC). Understanding the hematologic findings of patients with SARS-CoV-2 infection is essential to promote their care and improve outcomes. Objective:In this review, we aim at summarizing changes in the hematopoietic system and hemostasis that occur in SARS-CoV-2 infected patients. Findings: COVID-19 infection is often associated with laboratory hematologic findings that can have important clinical implications. Careful revision of baseline hematologic findings at diagnosis can predict severity of illness and help clinicians tailor their management and approach to patients whose condition can be guarded or critical.This can be of therapeutic and prognostic value in severely ill patients and can reduce the mortality rate from COVID-19. Such markers include D-dimer, procalcitonin, C-reactive protein, viral load, cytokine storm, and lymphopenia.Studies have also shown an association between these markers and severe COVID-19 infection requiring admission to the intensive care unit or complicated by acute respiratory distress syndrome (ARDS). According to the American Society of Hematology (ASH), all hospitalized patients with COVID-19 should receive pharmacologic thromboprophylaxis with LMWH. Conclusion:Until more data arises, the summary we provide can be used by hematologists to better understand hemostasis in COVID-19 infected patients.We are in need for more studies to define appropriate management plans in the setting of hematologic findings.